Integrating CRISPR-Cas9 Technology into Undergraduate Courses: Perspectives from a National Science Foundation (NSF) Workshop for Undergraduate Faculty, June 2018 - Michael J. Wolyniak (American Society for Microbiology, 2019)
As CRISPR (clustered regularly interspaced short palindromic repeats)-Cas9 technology becomes more mainstream in life science research, it becomes critical for undergraduate instructors to devise engaging ways to bring the technology into their classrooms. To help meet this challenge, the National Science Foundation sponsored a workshop for undergraduate instructors in June 2018 at The Ohio State University in conjunction with the annual Association of Biology Laboratory Educators meeting based on a workflow developed by the workshop’s facilitators. Over the course of two and a half days, participants worked through a modular workflow for the use of CRISPR-Cas9 in a course-based (undergraduate) research experience (CURE) setting while discussing the barriers each of their institutions had to implementing such work, and how such barriers could be overcome. The result of the workshop was a team with newfound energy and confidence to implement CRISPR-Cas9 technology in their courses and the development of a community of undergraduate educators dedicated to supporting each other in the implementation of the workflow either in a CURE or modular format. In this article, we review the activities and discussions from the workshop that helped each participant devise their own tailored approaches of how best to bring this exciting new technology into their classes.